Prevalence and Determinants of Anemia among Adult Males in a Rural Area of Haryana, India - Shashi Kant; Rakesh Kumar; Sumit Malhotra; Ravneet Kaur; Partha Haldar (Journal of Epidemiology and Global Health, 2019)
Anemia is an under-recognized morbidity among adult males causing significant productivity loss. A study was done among adult males (≥18 years) in a rural area of Haryana, India to estimate the prevalence and determinants of anemia and to explore their attitude and beliefs about anemia. Mixed methods approach was adopted. A total of 1219 participants were selected by multi-stage simple random sampling for the cross-sectional study and were administered a questionnaire followed by hemoglobin measurement using HemoCue method. Six focus group discussions were conducted. Age adjusted prevalence of anemia was 27.9% [95% confidence interval (95% CI): 27.4–28.4%]. Anemia was found to be positively associated with age more than 50 years (OR: 2.7 (95% CI: 1.7–4.2) in age group 50–59 years and 3.6 (95% CI: 2.3–5.6) in age group ≥60 years as compared with age group 18–24 years) and presence of chronic co-morbidity (OR: 2.0; 95% CI: 1.2–3.2). There were misconceptions among study participants about the role of specific dietary factors in causation of anemia. Poor purchasing capacity was cited as main reason for not consuming iron rich diet. Anemia was a common morbidity in this study population.